Statistical evidence linking the zigzag stem habit with tolerance to cassava brown streak disease - Kanju, E.; Mkamilo, G.S.; Mgoo, V.; Ferguson, Morag E. (2010)
Cassava (Manihot esculenta Crantz) provides the cheapest source of food calories in Africa and forms the major staple for roughly 40% of Africans. More than 200 million people in sub-Saharan Africa derive over 50% of their carbohydrate intake from cassava. It has been recognised as a powerful poverty fighter with the potential to help alleviate poverty both through food security and commercialization...